Can 5‐month‐old infants consider the perspective of a novel eyeless agent? New evidence for early mentalistic reasoning. Issue 2 (12th November 2021) - Choi, Youjung; Luo, Yuyan; Baillargeon, Renée
Abstract: Is early reasoning about an agent's knowledge best characterized by a mentalistic stance, a teleological stance, or both? In this research, 5‐month‐old infants ( N = 64, 50% female, 83% White) saw a novel eyeless agent consistently approach object‐A as opposed to object‐B. Although infants could always see both objects, a screen separated object‐B from the agent. When object‐B protruded above the screen, infants interpreted the agent's actions as revealing a preference for object‐A over object‐B. When object‐B did not protrude above the screen, however, infants refrained from attributing such a preference: Consistent with mentalistic accounts, they reasoned that the agent's representation of the scene did not include object‐B, and they used the agent's incomplete representation, non‐egocentrically, to interpret its actions.